Analisis Kasus Bullying Pada Remaja Ditinjau Dari Perspektif Interaksionisme Simbolik - Didit Kurniawan Wintoko; Jason Marcelino Nugroho (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This paper aims to present an analysis of bullying that occurs in adolescents using the perspective of symbolic interactionism. The perspective focuses on social interaction, process, and meaning construction. This paper also discusses the complexity of bullying issues sociologically. The definition of bullying eventually becomes dynamic and is influenced by the process of observers in seeing the social interactions that occur. The factor of bullying becomes a crucial variable to fully understand the occurrence of bullying in adolescents. This paper uses qualitative research with a phenomenological approach with purposive sampling technique. The case study was conducted on students of the Faculty of Social and Political Sciences, University of Jember.